Arthroscopic Manifestations of Internal Temporomandibular Joint Disorders in Patients with Traumatic Fractures of the Mandibular Condylar Head - Khasapetov , Benik (The Ukrainian Scientific Medical Youth Journal, 2025)
the aim of this study was to evaluate the nature and severity of post-traumatic changes in the temporomandibular joints (TMJ) using arthroscopy in patients with П(MCHF) during the early and late post-traumatic periods. The study included 26 patients with 36 MCHF fractures of types B and C (according to Neff et al., 2004) with displaced fragments, who underwent open reduction, fragment fixation via osteosynthesis, and a secondary surgical intervention 4.2±1.2 months later for the removal of fixators and revision of surrounding soft tissue structures. The surgeries were performed under general anesthesia using a retroauricular approach. Prior to capsule incision, an arthroscope (KARL STORZ 1.9 mm, Germany) was inserted into the upper joint compartment to assess soft tissue structures such as the posterior joint ligament, disc, and joint capsule, as well as the cartilaginous lining of the articular fossa and eminence, using the standard posterior superior-lateral technique. Intraoperative arthroscopy performed during fragment reduction and fixation revealed intra-articular abnormalities in all 26 patients, primarily related to acute TMJ trauma and, to a lesser extent, to pre-existing morphological changes of the joint elements. In the area of the posterior joint ligament and medial portions of the capsule, hyperemia (86.1%) and pronounced vascular injection (58.3%) were observed, indicating the development of synovitis in the majority of patients. Furthermore, all patients had disc displacement, with anterior and medial dislocation, accompanied by a small fragment of the fractured mandibular head. The integrity of the disc was preserved in all cases. Hemarthrosis (blood clots and hemorrhages) in the upper compartment of the joint cavity was present in 52.7% of cases. Hyperplastic synovitis and synovial polyps were observed in 13.04%, while isolated adhesions, fibrils on the surface of connective tissue cartilage, and fibrous exudate/debris were identified in 34.78% of patients, primarily in older individuals, indicating previous TMJ issues. In patients during fixator removal, TMJ changes were more related to post-traumatic remodeling processes and phenomena typical of degenerative processes. Hyperemia of the capsule and vascular injection in the retrodiscal ligament area were observed less frequently, in only 16.67% of patients. In contrast, signs of early osteoarthritis, such as fibrinous effusion in the joint cavity, fibrils on the surface of fibrocartilage, adhesions, and scarring of the capsule, were present in various combinations and degrees of expression in 100% of patients. Productive synovitis and synovial polyps were observed in 25% of patients. After osteosynthesis, disc repositioning was achieved in all cases, and the disc remained in the joint cavity 4 months post-surgery, confirming the effectiveness of the surgical method in restoring normal anatomical relationships in the TMJ, and eliminating the need for additional disc fixation in the majority of MCHF fractures of types B and C. TMJ arthroscopy is a reliable method for diagnosing intra-articular disorders in traumatic MCHF and can be considered a therapeutic tool for managing pathological processes in both the early and late postoperative periods, with the goal of preventing their progression and achieving full functional rehabilitation of the affected patients.